Needlestick and Sharp Injuries among Healthcare Workers in the Operating Theatre: Why They Do Not Report Their Incidences (The International Journal for Scientific Research, 2023)
Introduction: Needlestick and Sharp Injuries (NSSIs) pose a significant threat to healthcare workers, particularly in Operating Theatres (OTs), where the risk of exposure is compounded by high-stress environments and the complexity of procedures. Despite the known dangers, a persistent issue of underreporting complicates efforts to safeguard worker and patient health. This paper promotes the adoption of Evidence-Based Practice (EBP) to mitigate these risks, aiming to improve reporting behaviors and, by extension, overall safety within healthcare settings. Methods: This study utilizes a qualitative research approach, combining literature review and case studies to explore the phenomena of NSSI underreporting among healthcare workers. It examines barriers to reporting within OTs, such as fear of repercussions and time constraints, and proposes interventions based on EBP. Research methodology emphasizes the application of theory to practice through multidisciplinary team involvement, workshops, and the establishment of clear, achievable goals. Results: The investigation reveals that while healthcare workers are generally aware of the protocols for reporting NSSIs, a range of barriers inhibits consistent application in practice. The study identifies effective strategies for bridging the theory practice gap, including fostering a constructive learning environment, ensuring leadership support, and promoting open communication. These strategies are shown to facilitate the practical application of theoretical knowledge, thereby improving reporting rates and enhancing safety protocols in OTs. Conclusions:  Effectively addressing NSSIs in healthcare settings, particularly in Operating Theatres, requires a comprehensive approach that encompasses education, clear reporting protocols, and a culture of collective responsibility. Bridging the gap between theoretical knowledge and practical application through workshops, evidence translation, and an emphasis on interdisciplinary collaboration is key to enhancing patient and worker safety. The study underscores the necessity of understanding the multifaceted nature of behavior change in healthcare environments to implement successful EBP strategies.
Keywords: Needlestick Injuries; Operating Theatres; Underreporting; Evidence-Based Practice; Theory-Practice Gap